2010
DOI: 10.4314/gmj.v43i3.55326
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the knowledge, practice and perceptions of contraception in rural southern Nigeria

Abstract: SUMMARYBackground: Significant proportion of maternal deaths in Nigeria is due to complications of unsafe abortions, and these abortions are responses to unwanted pregnancies that could have been prevented by effective contraceptive programming. Despite intense programmatic efforts by the Nigerian government and various non-governmental agencies to reverse the trend, there has been little evidence to suggest a systematic improvement in these indicators. Methodology: A household random survey of 1,528 women age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 11 publications
(10 reference statements)
8
46
2
Order By: Relevance
“…Other studies by Jabbar FAet al and Khawaja et al, have also noticed similar findings in which multimedia and family planning workers were the main sources of knowledge regarding contraception in the community 4,13 . In contrast to our findings, other studies reported relatives and friends being the major source of information 14,15 . Overall, the media seems to play a major role in providing information regarding contraception and could do more by spreading practical information.…”
Section: Resultscontrasting
confidence: 99%
“…Other studies by Jabbar FAet al and Khawaja et al, have also noticed similar findings in which multimedia and family planning workers were the main sources of knowledge regarding contraception in the community 4,13 . In contrast to our findings, other studies reported relatives and friends being the major source of information 14,15 . Overall, the media seems to play a major role in providing information regarding contraception and could do more by spreading practical information.…”
Section: Resultscontrasting
confidence: 99%
“…high awareness but low utilization of contraceptives, making this situation a serious challenge in developing countries. 7,8 In present study emergency contraception (3%) was the least used contraceptive methods which is similar to the study by Tizta et al 5 This fact emphasizes that there need to be effective strategies to disseminate information regarding various methods of contraception. 9.37% of the women who have studied upto high school had not taken any contraception compared to study Gaikwad S et al where in from the group of studied women 38.23% did not use any contraceptive methods.…”
Section: Discussionsupporting
confidence: 88%
“…They believe that those who use modern family planning methods are interfering with nature and they may be punished with infertility on re-incarnation. Same has been reported by Lawrence in 2009 from Nigeria 21 .…”
Section: Discussionsupporting
confidence: 57%